A modern approach to the treatment of acute low back pain: a proposal of a new treatment algorithm - Robert Rupiński; Urszula Grata-Borkowska; Jarosław Drobnik (Family Medicine & Primary Care Review)
Acute low back pain is a common cause of disability in the general population. Effective pain management, which prevents the transition from acute to chronic pain, is essential in its treatment and primarily involves the use of non-steroidal anti-inflammatory drugs (NSAIDs) and physical medicine modalities, including heat therapy. In recent years, the option of home treatment with low-intensity heat therapy using a convenient heat wrap has become available. Locally applied low-intensity heat therapy for acute lower back pain has an analgesic effect and reduces paraspinal muscle tension. Several randomized clinical trials have demonstrated the efficacy of this method in reducing pain and disability to a degree comparable to high-dose NSAID therapy. Based on this evidence, it now appears that routine therapeutic management of acute low back pain can be modified by combining standard NSAID therapy with the application of a thermal compress. The essence of this change involves incorporating heat wrap for 2–4 days (8 hours daily) before modifying NSAID dosage or implementing another therapeutic option. Considering the clinical studies on low-intensity heat in acute lower back pain, a reduction of at least 25% in NSAID dosage can be expected. We propose that treatment with a new therapeutic method, which is low-intensity heat therapy, should be an addition to the previously applicable standards, the effectiveness of which was unsatisfactory. The aim of introducing low intensity heat therapy is to reduce the use of NSAIDs (and thus reduce the chance of adverse effects) and to shorten the duration of therapy.